Effect of fiscal incentives on coal bed methane price: a hypothetical analysis - Makmun, Makmun; Sitepu, Eddy Mayor Putra (P2E-LIPI, 2012)
Fossil fuel reserves are diminishing and coal bed methane (CBM) has been regarded as a potentialreplacement energy source because Indonesiaâs CBM reserves are enormous, up to 453 trillion cubicfeet. To boost investment in CBM development in Indonesia, support in the form of fiscal incentivesis needed. By analysing the effects of incentives on CBMâs selling price this study assesses whether theforms of incentives provided by the government so far have been appropriate and sufficient. This studyuses economic modelling to calculate the effect of incentives on the economics of CBM developmentin Indonesia. The results of this study show that incentives will have a significant effect on CBMâseconomic price if there is a composite of different forms of incentive. Nevertheless, in implementingan incentives policy it is important to consider the effect fiscal incentives will have on the reduction ofthe subsidy for electricity.Keywords: CBM, Fiscal incentive, Economic price